The Gendered Profession : The Case Of Nursing In Turkey - Kasapoglu, Aytul; Akbal, Alev (Advances in Social Sciences Research Journal, 2017)
Health and illness are flip sides of the same coin. Similarly, patients and health care providers are inseparable and interlocking elements integrated into the same context. The key concept is the caring interaction, and there is a positive association between satisfaction and caring interactions. Although care providers’ satisfaction affects the quality of care, patient satisfaction determines the quality of nursing care in terms of “relational theory,” embedded in socialist feminist thought. The primary aim of this study was to contribute to gender studies – in addition to health care and nursing studies – by exploring and describing job dissatisfaction and frustrations among nurses in Turkey. In addition, the metaphor of marriage was proposed to elucidate the nurses’ situation in society, which is in line with a socialist feminist perspective and to fulfil requirements of grounded theory methodology. This study explored the following research questions: What are the basic sources of dissatisfaction from the nurse’s perspective? What is the utility of the feminist perspective and grounded theory methodology in investigating the sources of dissatisfaction amongst nurses? Interviews were conducted with nurses and patients at the Rehabilitation and Care Centre of the Turkish Military Forces. The findings revealed that nurses are exposed to many organisational, professional and patient-based pressures and that the image of nurses occupying a low status in society was a particularly salient core concept, amongst others. The findings also revealed that the overwhelmingly female-dominated nursing profession in Turkey is undercompensated and beset with unrealistic expectations due to a lack of specialisation and professionalization. Empowering nurses means communicating that caregiving is valued, while strengthening current nurses both at home and at work without resorting to male comparisons.